Principles of business forecasting - Ord, J. K. (South-Western Cengage Learning, 2013)
Suitable for users who have taken a first course in applied statistics or have an equivalent background, this book provides an introduction to both standard and advanced forecasting approaches. It presents general principles that are the basis of forecasting practice.